1990
DOI: 10.4141/cjas90-046
|View full text |Cite
|
Sign up to set email alerts
|

Social Stress and Dominance Among Group Members After Mixing Beef Cows

Abstract: dominance among group members after mixing beef cows. Can. J. Animal Sci. 70t [345][346][347][348][349][350][351][352][353][354].

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
20
1
1

Year Published

1991
1991
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(24 citation statements)
references
References 20 publications
2
20
1
1
Order By: Relevance
“…This is likely more evident in situations where home range areas overlap because of small pasture sizes and where dominance hierarchies are well established because the individual composition of the herd remains relatively constant (e.g., CRLRC). Periodic rotation among pastures also may affect the strength of social associations and fidelity to sub-groups, because cattle adapt to regrouping events [48]. When cattle are moved among smaller pastures, cattle become mixed and there is less time for spatial home range preferences to develop, or corresponding isolation among individuals.…”
Section: Number Of Gps-tracked Animalsmentioning
confidence: 99%
“…This is likely more evident in situations where home range areas overlap because of small pasture sizes and where dominance hierarchies are well established because the individual composition of the herd remains relatively constant (e.g., CRLRC). Periodic rotation among pastures also may affect the strength of social associations and fidelity to sub-groups, because cattle adapt to regrouping events [48]. When cattle are moved among smaller pastures, cattle become mixed and there is less time for spatial home range preferences to develop, or corresponding isolation among individuals.…”
Section: Number Of Gps-tracked Animalsmentioning
confidence: 99%
“…A chronic stressor, such as mixing of cattle (Mench et al 1990) or penning (Friend et al 1985), causes an increase in plasma cortisol over trme. An acute stressor causes a raoid increase in the concentration of olasma adrenal corticosteroids which steadily decline to homeostatis (Stott 1981 (Hargreaves and Hutson 1990).…”
mentioning
confidence: 99%
“…(Sowerby and Poland, 1978) did not find any consistent effect of group size during grouping. (Mench et al, 1990) found a relatively low amount of fights between unfamiliar beef cows that were grouped in the third trimester of pregnancy compared to earlier studies and suggest this could be an effect of late pregnancy. However, introducing heifers in late pregnancy into a cow herd of different stages of lactation may have different effects and there might be the risk for premature parturition.…”
Section: Management Of the Social Groupmentioning
confidence: 61%